bifA Regulates Biofilm Development of Pseudomonas putida MnB1 as a Primary Response to H2O2 and Mn2+ - Zheng, Yanjing; Li, Yumei; Long, Hongyan; Zhao, Xiaojuan; Jia, Keke; Li, Juan; Wang, Leyong; Wang, Ruiyong; Lu, Xiancai; Zhang, Dongmei (Frontiers in Microbiology, 2018)
PPseudomonas putida (P. putida) MnB1 is a widely used model strain in environment science and technology for determining microbial manganese oxidation. Numerous studies have demonstrated that the growth and metabolism of P. putida MnB1’s are influenced by various environmental factors. In this study, we investigated the effects of hydrogen peroxide (H2O2) and manganese (Mn2+) on proliferation, Mn2+ acquisition, anti-oxidative system, and biofilm formation of P. putida MnB1. The related orthologues of 4 genes, mco, mntABC, sod, and bifA, were amplified from P. putida GB1 and their involvement were assayed, respectively. We found that P. putida MnB1 degraded H2O2, and quickly recovered for proliferation, but its intracellular oxidative stress state was maintained, with rapid biofilm formation after H2O2 depletion. The data from mco, mntABC, sod and bifA expression levels by qRT-PCR, elucidated a sensitivity toward bifA-mediated biofilm formation, in contrary to intracellular anti-oxidative system under H2O2 exposure. Meanwhile, Mn2+ ion supply inhibited biofilm formation of P. putida MnB1. The expression pattern of these genes showed that Mn2+ ion supply likely functioned to modulate biofilm formation rather than acting as nutrient substrate for P. putida MnB1. Furthermore, blockade of BifA activity by GTP increased the formation and development of biofilms during H2O2 exposure, while converse response to Mn2+ ion supply was evident. These distinct cellular responses to H2O2 and Mn2+ provide insights on the common mechanism by which environmental microorganisms may be protected from exogenous factors. We postulate that BifA-mediated biofilm formation but not intracellular anti-oxidative system may be a primary protective strategy adopted by P. putida MnB1. These findings will highlight the understanding of microbial adaptation mechanisms to distinct environmental stresses.